Dynamiques identitaires anciennes et actuelles chez les Aché du Paraguay oriental : éléments de compréhension - Philippe Edeb Piragi (Journal de la Société des Américanistes)
Keys to understanding ancient and current identity dynamics among the Ache of Eastern Paraguay. Based on fieldwork begun in 1986, the author analyses the driving forces behind Aché self-assertion, exploring the conceptions of self and other of this Eastern Paraguayan group of tupi speakers who have repeatedly and successfully resisted assimilation by the Guarani. Following forced settlement in Mission-run reservations which was completed in 1978, older geopolitical segmentations were replaced by a new distribution of this nomadic society in permanent and independent colonies. Loss of ancestral territory dismembered the former socio-political unit, ache gatu, which was a crucial component of ethnic identity for the Southern and Northern groups. The return of people raised as captives among the Whites also had a great sociological impact, adding complexity to Aché knowledge and the challenges that awaited them. However, resurgence of ethnic and territorial claims, apparent since 2000, led to the federation, in 2008, of the four last remaining ache gatu sub-groups, who managed to retain yet supersede their traditional linguistic and cultural differences to assert themselves as one People, in itself and for itself.